Shoulder internal and external rotation range of motion in nationally ranked junior tennis players: A longitudinal analysis - Roetert, E. P.; Ellenbecker, T. S.; Brown, S. W. (The Journal of Strength and Conditioning Research, 2000)
This study longitudinally examined shoulder internal rotation (IR), external rotation (ER), and total rotation (TROT) in the dominant (D) and nondominant (ND) arms of 44 nationally ranked junior tennis players aged 14-17 years. Analyses conducted across the 4 age groups revealed a significant main effect of age for IR ranges of motion (ROMs; p < 0.05) but not for ER ROMs. Follow-up analyses on D, IR ROMs revealed a significant increase between age 14 and both ages 15 and 16 (p < 0.05) and revealed a slight decrease at age 17. Follow-up analyses for ND, IR ROMs showed no significant difference between ages 14 and 15 but showed a significant difference between age 14 and both ages 16 and 17 (p < 0.05). An additional analysis conducted on TROT revealed a significant main effect of age for ND ROMs (p < 0.05) but not for D ROMs. The results suggest a significant increase in ND, TROT ROMs between ages 14 and 16 that subsequently remains stable.